Uma análise sobre o trabalho dos conselheiros municipais de educação de Nova Ponte-MG - Silva, Mara Rubia Aparecida da (2019)
This research aimed to analyze the participation and work of the municipal councilors of education of Nova Ponte from 2017 to 2019 and their possibilities of social control and democratization. To achieve this goal we use content analysis as a methodology. Data collection occurred through the analysis of documents, interviews, laws and minutes of the Nova Ponte Municipal Education Council. In this study, we bring the question about the participation and the work found in the Municipal Councils of Education, being this an important space to reflect several actions, which often have the characteristic of advising the government, we will also enter in this study the Marxian categories that discusses the work in face of the reality of capitalism, in its inherent inequality, we present a study seeking to think about the sociopolitical issue in its possibilities and limits with regard to the performance of the Nova Ponte Municipal Education Council, following critically the actions aimed at citizenship, and we will look at how the Council can become a communicator between civil society and the state.